2017
DOI: 10.1139/cjm-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

From source to filter: changes in bacterial community composition during potable water treatment

Abstract: Rural communities rely on surface water reservoirs for potable water. Effective removal of chemical contaminants and bacterial pathogens from these reservoirs requires an understanding of the bacterial community diversity that is present. In this study, we carried out a 16S rRNAbased profiling approach to describe the bacterial consortia in the raw surface water entering the water treatment plants of two rural communities. Our results show that source water is dominated by the Proteobacteria, Bacteroidetes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…In line with other studies (Pinto et al, 2012;Prest et al, 2014;Wu et al, 2015) phyla such as Proteobacteria, Actinobacteria, Firmicutes, Cyanobacteria, Bacteroidetes, and Nitrospirae were commonly found in the water samples investigated. As also observed in this study, several studies have identified Proteobacteria as the most abundant phylum in aquatic environments within the drinking water production industry (Bautista-de los Santos et al, 2016;El-Chakhtoura et al, 2015;Liu et al, 2014;Vaz-Moreira, Nunes, & Manaia, 2017;Zanacic, McMartin, & Stavrinides, 2017). It is clear from our results that the bacterial community composition of surface water strongly differs from those of the other water types studied.…”
Section: (A) (B)supporting
confidence: 82%
“…In line with other studies (Pinto et al, 2012;Prest et al, 2014;Wu et al, 2015) phyla such as Proteobacteria, Actinobacteria, Firmicutes, Cyanobacteria, Bacteroidetes, and Nitrospirae were commonly found in the water samples investigated. As also observed in this study, several studies have identified Proteobacteria as the most abundant phylum in aquatic environments within the drinking water production industry (Bautista-de los Santos et al, 2016;El-Chakhtoura et al, 2015;Liu et al, 2014;Vaz-Moreira, Nunes, & Manaia, 2017;Zanacic, McMartin, & Stavrinides, 2017). It is clear from our results that the bacterial community composition of surface water strongly differs from those of the other water types studied.…”
Section: (A) (B)supporting
confidence: 82%
“…However, this study also showed that the ARG composition was identical when comparing raw and tap water samples: β-lactams (19%), macrolides (13%), fluoroquinolones (9%), and glycopeptides (3%) were most prevalent, and there was a greater ARG diversity in the raw water sample versus the tap water sample ( 31 ). Similarly, an increase in pathogen detection was reported after water treatment in two rural Saskatchewan, Canada, villages ( 32 ). Taken together, water distribution systems may be an important source of pathogen contamination that then leads to issues where the water is delivered.…”
Section: Discussionmentioning
confidence: 70%
“…An activated carbon filtration system incorporated in the device improves the treatment of drinking water; sometimes an Ag + coating may be present. The activated carbon filter is used for a bacteriostatic effect and to reduce tastes and odors or remove organic and inorganic contaminants [6,7]. Furthermore, the use of activated carbon filters could amplify the microbiological contamination at point of use, especially in the presence of water stagnation [8,9].…”
Section: Introductionmentioning
confidence: 99%